EDUKASI MITIGASI BENCANA PADA MASYARAKAT DI PESISIR PANTAI BAHARI, KABUPATEN POLEWALI MANDAR - Firmansyah; Lala (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This community service program aims to enhance the capacity and preparedness of residents and visitors at Bahari Beach, Polewali Mandar Regency, in facing potential coastal disasters such as earthquakes, tsunamis, and abrasion. The methods applied include interactive socialization, evacuation drills, distribution of educational media, and tree planting as physical mitigation. The results indicate a significant improvement in the community’s understanding of disaster signs, evacuation routes, and self-rescue measures. Active community participation demonstrates that this educational program is effective in fostering a disaster-preparedness culture. Similar programs are recommended in the future to ensure the sustainability of the positive impacts achieved.